Osteopathology of the jaw associated with bone resorption inhibitors: what have we learned in the last 8 years? (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: 8 years after discovery of osteonecrosis of the jaw associated with bisphosphonate therapy a lot of experience has been garnered in treating 112 patients with this disease. This disease, although uncommon, is still a burden for the patient as well as the treating specialists and an adequate standardised classification as well as therapy does not exist. This article presents a summary of collected patient data, garnered experience and consequential changes in knowledge, in diagnostic measures and therapy. METHODS: The data of in total 112 patients referred to the Special Clinics for patients with bisphosphonate-associated lesions of the jaw was retrospectively analysed and compared with data from the literature. RESULTS: In total, 110 patients, 70% women, were included in the data analysis. A quarter of those patients had osteoporosis as the underlying disease, more than half of all patients had extractions as the local influencing factor. The lesion was localised in the mandible in three quarters of all patients and almost all patients showed clinical signs of infection. In total, 58% of all patients were treated surgically with a complete remission rate of 78% over 7 years. CONCLUSIONS: This summary of patient data and literature shows that knowledge about bisphosphonate-associated osteopathology of the jaw becomes more and more specific. The range of drugs associated with this disease has increased, but also therapeutic options show more and more success. Classifications, published shortly after the discovery of BRONJ need to be revised and new knowledge included.